2010
DOI: 10.1007/s11605-010-1256-1
|View full text |Cite
|
Sign up to set email alerts
|

Living Donor and Deceased Donor Liver Transplantation for Autoimmune and Cholestatic Liver Diseases—An Analysis of the UNOS Database

Abstract: The overall survival outcomes of LDLT were similar to DDLT in our patients with autoimmune and cholestatic liver diseases. It appears from our study that after adjusting for age and MELD score donor type does not significantly affect the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
2
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 26 publications
3
42
2
5
Order By: Relevance
“…There was substantial improvement over time, and superior outcomes of LDLT in autoimmune hepatitis and cholestatic liver disease at experienced centers (12). Kashyap et al performed a retrospective analysis of US national data for patients transplanted between February 2002 and October 2006, and demonstrated higher unadjusted survival after LDLT compared to DDLT; for patients with autoimmune hepatitis, PSC, and PBC, they found similar outcomes for the two graft types after adjusting for covariates (14). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was substantial improvement over time, and superior outcomes of LDLT in autoimmune hepatitis and cholestatic liver disease at experienced centers (12). Kashyap et al performed a retrospective analysis of US national data for patients transplanted between February 2002 and October 2006, and demonstrated higher unadjusted survival after LDLT compared to DDLT; for patients with autoimmune hepatitis, PSC, and PBC, they found similar outcomes for the two graft types after adjusting for covariates (14). …”
Section: Discussionmentioning
confidence: 99%
“…Early reports demonstrating inferior outcomes in LDLT compared to DDLT (5), and donor morbidity and mortality may have contributed to the limited growth in North America (6, 7). As experience increased, early post-transplant outcomes improved and single center reports demonstrated similar or even better outcomes of LDLT compared to DDLT (811), and recent registry studies have demonstrated comparable outcomes between LDLT and DDLT across many indications (1214). Analyses from large unfunded registries, however, provide less detailed information than is possible from a federally supported multicenter observational cohort study.…”
Section: Introductionmentioning
confidence: 99%
“…The overall patient and graft 5-year survival rates in PSC recipients are excellent: 95.4% and 89.6%, respectively[83]. Patients receiving transplants for PSC have disease-specific complications (excluding the usual post-transplant complications) that might lead to increased morbidity and mortality rates.…”
Section: Psc After Liver Transplantationmentioning
confidence: 99%
“…In a subsequent paper the same group compared the survival outcome of PSC patients either receiving a live or a deceased donor allograft using the United Network for Organ Sharing (UNOS) database [17]. On multivariate analysis, after adjusting for age and MELD score, the type of donor was not found to be statistically significant.…”
Section: Recurrent Primary Sclerosing Cholangitis In Live Donor Livermentioning
confidence: 99%